The scholarship of inter-faith engagement in the writings of selected contemporary Muslim scholars - Shehu, Fatmir (Usuli Faqih Research Centre PLT, 2017)
The acts of pride, arrogance, superiority, selfishness, enmity and disrespect to others have created since the very beginning of human history a very hostile environment. It has been an immense obstacle for the construction of a friendly and mutual engagement among people. Such engagement can take place in different aspects of peoples’ daily activities, like religious, civilizational, political, sociological, cultural, economic and so on. The most important engagement concerning peoples’ spiritual and material aspects of life, is inter-faith engagement. The thrust of this study will be on the scholarship of inter-faith engagement in the writings of four selected contemporary Muslim scholars - Ismacil Raji al-Faruqi, Murad Wilfried Hofmann, cIrfan cAbdul Hamid Fattah and Mahmoud Ayoub. Inter-faith engagement as a scholarship has been introduced in our contemporary time. But the guidelines for this scholarship have been addressed in the Quran and applied by the Prophet (PBUH) fourteen centuries ago. Therefore, this paper has firstly attempted to discuss the scholarship of inter-faith engagement as promoted by the Quran and its application in the lifetime of Prophet Muhammad (PBUH). Secondly, the approaches of three selected contemporary Muslim scholars towards this scholarship have been explored and dealt with. The descriptive and analytical methods have been employed in the entire study. The findings of this study will assist people of different religious and cultural backgrounds to have better understanding of others while dealing with them.